1956
DOI: 10.1111/j.1476-5381.1956.tb01027.x
|View full text |Cite
|
Sign up to set email alerts
|

INACTIVATION OF ADRENALINE AND NORADRENALINE BY HUMAN AND OTHER MAMMALIAN LIVER IN VITRO

Abstract: In a previous paper, Bain, Gaunt, and Suffolk (1937) described a biological assay method for following the course of adrenaline inactivation in vitro. Using this method they showed, among other things: (1) that adrenaline was only partially inactivated in cats' defibrinated blood, and that this was largely owing to the slow passage of some of the adrenaline into the red cells, whence most of it could be recovered by laking; (2) that the addition of tissue slices, particularly of liver, to a blood-adrenaline mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1956
1956
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…At high frequencies the rate of noradrenaline release might exceed the maximum rate at which amine oxidase could destroy it. The accumulating transmitter would then spill over into the blood stream where it would be protected from destruction (Bain & Batty, 1956). This possibility was investigated by studying the effect of an inhibitor of monoamine oxidase on the output of sympathin at 10 and 30/sec.…”
Section: Effect Of the Frequency Of Stimulation On Outputmentioning
confidence: 99%
“…At high frequencies the rate of noradrenaline release might exceed the maximum rate at which amine oxidase could destroy it. The accumulating transmitter would then spill over into the blood stream where it would be protected from destruction (Bain & Batty, 1956). This possibility was investigated by studying the effect of an inhibitor of monoamine oxidase on the output of sympathin at 10 and 30/sec.…”
Section: Effect Of the Frequency Of Stimulation On Outputmentioning
confidence: 99%
“…To do this, four or more blood and adrenaline samples are removed for assay at times ranging from S to about 90 min. The adrenaline assay and the estimation of the adrenaline content of the mixtures are described in detail by Bain et al (1937) and by Bain and Batty (1956). When the log adrenaline concentration is plotted against time, as in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Bain et al (1937) used, as a measure of the rate of adrenaline inactivation, the time taken to inactivate half of the original amount present; Bain andBatty (1952, 1956) took the regression coefficient of log adrenaline concentration against time. We have estimated the rate of inactivation by calculating the amount of adrenaline destroyed in 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro experiments showed that 2c is readily oxidized by catechol oxidase, the cytochrome system, amine oxidases, and peroxidases (86). Javillier and Lavollay supposed that Vitamin P slowed down oxidation and thereby the resulting inactivation of 2c (49,(87)(88)(89); 2c can also be inactivated by non-oxidative enzymes, such as catechol-Omethyltransferase. The ability of many different types of flavonoids and coumarins to affect the persistence of 2c was evaluated in a subsequent extensive study (85).…”
Section: Early Ideas On the Mechanism Of Action Of Vitamin Pmentioning
confidence: 99%